Peran Fintech Dalam Meningkatkan Akses Keuangan Di Era Digital - Negarawati, Esa; Rohana, Siti (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
Financial Technology (FinTech) is an innovation in financial services that uses digital technology to provide easier, more efficient and affordable access. This article discusses the development of FinTech in Indonesia, including its role in increasing financial inclusion, providing digital banking services, electronic payments, and peer-to-peer lending business models. Through literature analysis, this article shows that FinTech has driven significant changes in financial access and interactions, especially for those in remote areas or without access to traditional financial services. Although FinTech offers many advantages, such as efficiency and ease of transactions, challenges such as limited access to technology and security risks still need to be overcome. Adaptive regulations and collaboration with traditional financial institutions are needed to maximize the potential of FinTech in supporting financial inclusion and sustainable economic development in Indonesia.